2020
DOI: 10.30560/as.v2n1p289
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Characters Association of Hot Pepper (Capsicum annuum L.) Genotypes Tested under Irrigation in Northern Ethiopia

Abstract: Hot pepper production in most areas of Ethiopia especially in Tigray region is constrained by shortage of varieties, the prevalence of fungal and bacterial as well as viral diseases. Sixty-four hot pepper genotypes were evaluated to obtain the extent of genetic variability, association among characters. The experiment was laid out using 8x8 simple lattice design at Axum Agricultural Research center in 2017/18. Data were collected for 19 agronomic characters and analysis of variance revealed significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…The highest and positive indirect genotypic effects on hot pepper yield exhibited by plant height, fruit weight, fruit length and fruit number per plant via marketable yield per hectare. The present finding is in agreement with the finding of Kumari (2017), [3,8,10] they reported that direct and indirect effect of different morph agronomic traits of hot pepper on its yield.…”
Section: Path Coefficient Analysissupporting
confidence: 94%
See 1 more Smart Citation
“…The highest and positive indirect genotypic effects on hot pepper yield exhibited by plant height, fruit weight, fruit length and fruit number per plant via marketable yield per hectare. The present finding is in agreement with the finding of Kumari (2017), [3,8,10] they reported that direct and indirect effect of different morph agronomic traits of hot pepper on its yield.…”
Section: Path Coefficient Analysissupporting
confidence: 94%
“…Similar finding was reported by Berhanu et al (2011) indicating that high GCV and PCV values for fruit weight, number fruits per plant. In addition, similar findings were also reported by [4,10].…”
Section: Estimation Of Variance Componentssupporting
confidence: 90%
“…In this study, all the traits had moderate (stem diameter, leaf width, day to harvest, number of fruits per plant, and fruit yield per plant) to high (plant height, dichotomous height, leaf length, day to flowering, fruit length and diameter, and fruit weight). From the study done by Belay et al (2020) dan Rosmaina et al (2016) this high heritability indicating that the traits were more influenced by genetic factors. Generally, characters like fruit length, fruit diameter, and fruit weight with high genetic variation and heritability should be considered as reliable selection criteria for yield improvement in chili pepper.…”
Section: Discussionmentioning
confidence: 96%
“…Hot pepper is highvalue crop important in the local dishes, Karia, berbere, and processing industries as a coloring agent and raw material for the export market in the form of oleoresin [3]. It was introduced to Ethiopia by the Portuguese in the 17 th century [4].…”
Section: Introductionmentioning
confidence: 99%